Pengembangan Bahan Ajar Teks Cerita Rakyat Bahasa Indonesia Berbasis Canva melalui Model Addie SMP Surabaya Grammar School - Rinasari, Erry Ratna Eka; Leksono, Ibut Priono; Rohman, Ujang (LP. Ma'arif Janggan Magetan, 2023)
The purpose of this study was to produce a Canva-based Indonesian Folklore Text Teaching Material in facilitating students as an interesting source of information with Indonesian subject matter so that it can improve student learning outcomes of Class VII SMP Surabaya Grammar School in teaching and learning activities in language subjects Indonesia. The research model used in this study is the ADDIE model. The selection of this model is based on the consideration that this model is easy to understand, developed systematically, and is based on the theoretical foundation of the developed learning design. This model is structured programmatically with systematic activities in an effort to solve learning problems related to learning media according to the needs and characteristics of students. The stages of research on the ADDIE model consist of five stages which include analysis, design, research, implementation, evaluation. The research process involved subject content experts, design experts and media experts to provide feedback, input and improvements. In addition, Indonesian language teachers and Surabaya Grammar School Middle School students as users of Canva-based Indonesian Folklore Text Teaching Materials also provided their comments and input. The use of Canva-based Indonesian Folklore Text Teaching Materials with the ADDIE model which consists of five stages which include analysis, design, research, implementation, evaluation for Indonesian subjects. which can effectively promote active and engaging learning. The results of this study are Canva-based Indonesian Folklore Text Teaching Materials which have a feasibility level of 95% for material, 94% for design feasibility, and 93% for media feasibility. While the small group trial rate is 90% and based on field trials 92% with very decent qualifications and does not need to be revised.